Analysis of PKN STAN Public Service Agency Innovations to Increase Non-Tax State Revenue - Satria Adhitama (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to analyze the innovations implemented by Politeknik Keuangan Negara STAN (PKN STAN) as a Public Service Agency to increase Non-Tax State Revenue. Methodology/Approach: This research uses a qualitative descriptive approach at PKN STAN, a higher education institution under the Ministry of Finance of the Republic of Indonesia with Public Service Agency status. Data were collected through interviews and were supported by official reports, documents, and regulations. Results/Findings: PKN STAN has implemented several innovations, including (1) collaborations in non-regular education with ministries, local governments, and international partners; (2) training programs using multipemda and multimitra schemes in partnership with universities, BLUs, BUMDs, and private companies; (3) consultancy and academic studies for public and private entities; and (4) public courses such as Tax Brevet A/B. These initiatives diversified income sources, reduced dependence on student admission fees (SPMB), and strengthened the Non-Tax State Revenue contributions. Limitations: This study was limited to one institution and used qualitative data, which may limit generalization. Detailed financial outcomes and long-term partner impacts were not analyzed in depth. Contributions: This study enriches the discussion on innovation and public financial management within BLUs. It offers insights for policymakers and higher education institutions to develop sustainable income diversification and innovation strategies. Conclusions: PKN STAN’s Public Service Agency status enables flexibility in resource management and fosters innovation to enhance Non-Tax State Revenue. Through partnerships, new training models, and academic service expansion, the institution exemplifies how innovation can support financial sustainability in public education. Ongoing evaluations and cross-institutional comparisons are recommended to strengthen best practices.